Writing and language learning advancing research agendas - Manchón, Rosa (Language learning and language teaching ;, 2020)
"The current volume aspires to add to previous research on the connection between writing and language learning from a dual perspective: It seeks to reflect current progress in the domain as well as to foster future developments in theory and research. The theoretical postulations contained in Part I identify and expand in novel ways the diverse lenses through which the varied, multi-faceted dimensions of the connection between writing and language learning can be explored. The methodological reflections put forward in Part III signal to theoretically-grounded and pedagogically-relevant paths along which future empirical work can grow. The empirical studies reported in Part II illuminate the myriad of individual, educational, and task-related variables that (may) mediate short-term and long-term language learning outcomes. These studies examine diverse forms of writing, performed in varied environments (including pen-and-paper and digital writing), conditions (writing individually and/or collaboratively), and instructional settings (academic settings - including secondary school and college level institutions - as well as out-of-school contexts)"--